THE INFLUENCE OF FISH OIL USING IN CHIKEN BROILER FEED ON NON CARCASS - I P. A. P., Setiawan; Astawa, I P. A.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 8 No 3 (2020): Vol. 8 No. 3 Tahun 2020; September - December, 2020)
This study aims to determine the effect of using fish oil in the ration on the percentage of non-carcass broiler chickens. This research was conducted in Dusun Pande, Dajan Peken Village, Tabanan Regency, for six weeks. The chicken used is a 2 week old broiler chicken. The design used was a completely randomized design (CRD) with three treatments and seven replications, each replication contained two broilers, so the number of chickens used was 42 chickens. The treatments were (P0) broiler chickens which were given feed with additional 0% fish oil, (P1) broiler chickens which were given feed with additional 3% fish oil and (P2) broiler chickens which were given feed with additional 6% fish oil. The variables observed were the percentage of heart, rampella, small intestine, liver, head, and feet. treatment P0 is 0.346%. The percentage of treatment heart (P2) 78.90% was significantly higher than that of treatment P0. The heart percentage of broiler chickens that received treatment (P1) was 16.76% higher than that of treatment P0, but it was not statistically significant, while the percentage of other non-carcasses (gizzard, small intestine, liver, head, and feet) showed no difference. the real one. Based on the results of the study, it can be concluded that the use of fish oil as much as 3% and 6% in the six-week old broiler ration could not affect the percentage of rampella, small intestine, liver, head and feet of broiler chickens, but there was an increase in the percentage of broiler chicken hearts in the use of fish oil. as much as 6%.   Keywords : broiler, non carcass, and fish oil